2006
DOI: 10.1111/j.1365-2486.2006.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term variation in the isotopic composition of organic matter allocated from the leaves to the stem of Pinus sylvestris: effects of photosynthetic and postphotosynthetic carbon isotope fractionation

Abstract: We aimed to quantify the separate effects of photosynthetic and postphotosynthetic carbon isotope discrimination on d 13 C of the fast-turn-over carbon pool (water soluble organic carbon and CO 2 emitted from heterotrophic tissues), including their diel variation, along the pathway of carbon transport from the foliage to the base of the stem.For that purpose, we determined d 13 C in total and water-soluble organic matter of the foliage plus d 13 C and d 18 O in phloem organic matter of twigs and at three heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
216
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(241 citation statements)
references
References 55 publications
22
216
3
Order By: Relevance
“…e.g. [72][73][74][75] Seasonal within-tooth variations may also be associated with shifts to different plant sources. Grasses and herbs tend to be slightly depleted in 13 C compared with trees.…”
Section: Carbon Isotope Resultsmentioning
confidence: 99%
“…e.g. [72][73][74][75] Seasonal within-tooth variations may also be associated with shifts to different plant sources. Grasses and herbs tend to be slightly depleted in 13 C compared with trees.…”
Section: Carbon Isotope Resultsmentioning
confidence: 99%
“…In the following synthesis we will explore step by step whether the Cres as compared to δ 13 C in phloem exudate and root water soluble organic matter in Triticum aestivum . Gessler et al (2009b) and Brandes et al (2006) showed that the δ 13 C of water soluble organic matter is a reasonably good proxy for δ 13 C of the neutral sugar fraction and thus the major respiratory substrate.…”
Section: M3: Flux Ratio Driven Variationsmentioning
confidence: 99%
“…Our understanding of these post-assimilation effects is rapidly progressing; however, it is premature for us to assess their magnitude without detailed isotopic flux and carbohydrate measurements (e.g. Badeck et al 2007;Barbour et al 2007;Brandes et al 2006;Bickford et al 2009). Stem tissues are particularly influenced by such post-photosynthetic metabolic effects, e.g.…”
Section: Patterns With Biomes and Vegetation Typementioning
confidence: 99%